PCR correction strategies for malaria drug trials: updates and clarifications. Issue 1 (January 2020) - Felger, Ingrid; Snounou, Georges; Hastings, Ian; Moehrle, Joerg J; Beck, Hans-Peter
Summary: Malaria drug trials conducted in endemic areas face a major challenge in their analysis because it is difficult to establish whether parasitaemia in blood samples collected after treatment indicate drug failure or a new infection acquired after treatment. It is therefore vital to reliably distinguish drug failures from new infections in order to obtain accurate estimates of drug failure rates. This distinction can be achieved for Plasmodium falciparum by comparing parasite genotypes obtained at the time of treatment (the baseline) and on the day of recurring parasitaemia. Such PCR correction is required to obtain accurate failure rates, even for new effective drugs. Despite the routine use of PCR correction in surveillance of drug resistance and in clinical drug trials, limitations inherent to the molecular genotyping methods have led some researchers to question the validity of current PCR correction strategies. Here we describe and discuss recent developments in these genotyping approaches, with a particular focus on method validation and limitations of the genotyping strategies. Our aim is to update scientists from public and private bodies who are working on the development, deployment, and surveillance of new malaria drugs. We aim to promote discussion around these issues and argue for the adoption of improved standardised PCR correction methodologies.